Penerapan Teknologi Digital Pada Administrasi Perkantoran - Fadillah, Apriliana Dian; Marsofiyati Marsofiyati (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The application of digital technology in office administration has a significant impact on work efficiency and productivity. This study aims to evaluate the effectiveness of the application of digital technology in office administration, identify the challenges faced, and the solutions that can be applied. The research method used is a qualitative approach with correlational analysis through literature review. The results of the study show that digital technology improves work efficiency, productivity, and the quality of office products. However, there are challenges in its application, such as the need for training and adaptation to new technology. The proposed solutions include improving the digital competence of employees and developing technology-based administration systems. This research is expected to provide insights for office practitioners in facing the digital era and improving the effectiveness of office administration.